AL-DIRÂSAH AL-DALÂLIYYAH FÎ TARJAMAH HURÛF AL-JARR AL-‘ARABIYYAH ILÂ AL-LUGHAH AL-MÂLÎZIYYAH - Muhamad Luqman Ibnul Hakim bin Mohd Saad; Marahaini Ahamad (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
This study was a descriptive and semantic analysis of the Arabic Prepositions من، إلى، عن، على، في، الباء، اللام translated into Malay language in the novel Masrur & Makrur. Its main aims are to identify the strategies and styles used to translate the prepositions and to analyze their meanings, semantic functions in verbal phrase (collocations and idioms) which were translated into Malay. This study applied the Dynamic, Semantic and Communicative Theories as well as the Relevance Theory to perform the analysis process. The results showed that the Arabic and Malay (translation) prepositions consisted of grammatical categories which cannot be translated into direct lexical. Instead, there was a need to look at sentence structure, syntax, grammatical rules, and semantics aspects as the more suitable contexts because these prepositions did not show their meanings unless they were used with other phrases.